LncRNA 3222401L13Rik Is Upregulated in Aging Astrocytes and Regulates Neuronal Support Function Through Interaction with Npas3 - Sophie Schröder; M. Sadman Sakib; Dennis M. Krüger; Tonatiuh Pena; Susanne Burkhardt; Anna-Lena Schütz; Farahnaz Sananbenesi; André Fischer (Non-Coding RNA, 2025)
Aging leads to cognitive decline and increased risk of neurodegenerative diseases. While molecular changes in central nervous system (CNS) cells contribute to this decline, the mechanisms are not fully understood. Long non-coding RNAs (lncRNAs) are key regulators of cellular functions. Background/Objectives: The roles of lncRNAs in aging, especially in glial cells, are not well characterized. Methods: We investigated lncRNA expression in non-neuronal cells from aged mice and identified 3222401L13Rik, a previously unstudied lncRNA, as upregulated in astrocytes during aging. Results: Knockdown of 3222401L13Rik in primary astrocytes revealed its critical role in regulating genes for neuronal support and synapse organization, a function conserved in human iPSC-derived astrocytes. A 3222401L13Rik interacts with the transcription factor Neuronal PAS Domain Protein 3 (Npas3), and overexpression of Npas3 rescues deficits in astrocytes lacking 3222401L13Rik. Conclusions: These data suggest that 3222401L13Rik upregulation may help delay age-related cognitive decline.